Mitochondrial respiratory activity and DNA damage in peripheral blood mononuclear cells in borderline personality disorder - Behnke, Alexander; Rappel, Manuela; Ramo-Fernández, Laura; Mavioğlu, R. Nehir; Weber, Benjamin; Neuner, Felix; Bisle, Ellen; Mack, Matthias; Radermacher, Peter; Witt, Stephanie; Schmahl, Christian; Karabatsiakis, Alexander; et al. (Psychological medicine, 2025)
BackgroundAlterations in the central and peripheral energy metabolism are increasingly recognized as key pathophysiological processes in psychiatric disorders. We investigated mitochondrial respiration and density linked to cellular energy metabolism and oxidative DNA damage in borderline personality disorder (BPD).MethodsThis cross-sectional case-control study compared three groups matched for age and body mass index: women with acute BPD, remitted BPD, and female healthy controls (n = 32, 15, 29). Peripheral blood mononuclear cells were investigated for differences in mitochondrial respiration, density, and markers of oxidative DNA damage.ResultsParticipants with acute BPD showed significantly reduced and less efficient mitochondrial ATP production compared to both remitted individuals and controls. Mitochondrial coupling and respiration were inversely associated with oxidative DNA damage, although DNA damage levels did not differ significantly across diagnostic groups. Sensitivity analyses indicated that comorbid major depressive episodes and antidepressant use did not account for the results.ConclusionsThese findings indicate mitochondrial alterations accompany acute symptom severity in BPD and may improve with remission. Unraveling causes and consequences of mitochondrial downregulation and its interplay with DNA maintenance in the context of stress and psychopathology could contribute to novel models and treatment strategies in BPD and related severe psychiatric disorders.